La comunidad y el Centro de difusión: Las dos caras del judaísmo ortodoxo. El caso de Jabad Lubavitch en Argentina - Setton, Eli Damian (2008)
This paper analyze the revival of Jewish orthodoxy in its double dimension: the community and the center of diffusion of Judaism. The first is linked to the religious conversion process (returning to the sources). The second one refers to the “proselytism” campaigns. The term Josid ties both dimension in the same identitary project. Analyzing the ceremony of farbrenguen (Hasidic meeting), and the meanings around the construction of the religious commandments legitimation, the paper focuses on the articulations between symbolic referents, taking up again the concept of compartimentalization and the question about the relationship between modernity and religion.